The escalation of the means of intrusion into the private sphere: starting from the Constitution - Fabio Alonzi (Revista Brasileira de Direito Processual Penal, 2019)
Articles 13, 14 and 15 of the Italian Constitution proclaim the “principles” of the inviolability of personal freedom, of domicile and communications by providing an articulated discipline that takes care of indicating the minimum conditions to tolerate invasive acts of these freedoms. The proliferation of new dangerous technological forms of dematerialized invasiveness of the personal sphere seem to undermine these constitutional protections that only a revitalization of the category of inviolability of the fundamental rights of the person allows to strengthen, providing at the same time the conceptual bases for the introduction and enhancement of new guarantee instruments such as “IT domicile”.